Comparison of the properties of silica aerogel doped with two different laser dyes: Crystal violet and Rhodamine B : DOI: 10.48129/kjs.20549 - Ahmed, Samah S.; Al-sharuee, israa F. (Kuwait Journal of Science, 2023)
In this paper, silica aerogel was doped with two laser dyes, Crystal violet and Rhodamine B, dissolved in ethanol. All samples were prepared in two different ways, with different concentrations and compared with non-doped prepared aerogel. The first way is the modification after the samples are converted to gel. The second way, the modification procedure, starts by adding the modified solution to the sol. TEOS was used as a precursor in two-step acid-base catalysis, and the silanol group trimethylchlorosilane + n-hexane was used as a surface modification. Fourier-transform infrared spectroscopy, field emission scanning electron microscope, X-ray diffraction, nitrogen adsorption-desorption isotherm, and contact angle measurements compared the characterization and structural properties of the two dyes. Results indicate that crystal violet gives better than Rhodamine B, as the contact angle measurement was 153°, total pour volume was 1.066 cm3/gm and the surface area was more significant than 970 m2/gm. While for Rhodamine B, the maximum contact angle was 146°, and the largest surface area was 899 m2/gm. And total pour volume was 1.6 cm3/gm.